Антология выдающихся достижений в науке и технике. Часть 33: Электромагнитная совместимость и защита от воздействия мощных электромагнитных помех радиоэлектронного, электротехнического и электроэнергетического оборудования - Баранов, М.И. (Електротехніка і електромеханіка, 2016)
Приведен краткий аналитический обзор основных научно-технических достижений в области электромагнитной
совместимости технических средств, методов и устройств защиты радиоэлектронного, электротехнического и
электроэнергетического оборудования от внешнего воздействия на него мощных импульсных электромагнитных помех, содержащих высокие напряжения, большие токи и сильные электромагнитные поля Наведено короткий аналітичний огляд основних науково-технічних досягнень в галузі електромагнітної сумісності
технічних засобів, методів і пристроїв захисту радіоелектронного, електротехнічного і електроенергетичного обладнання від зовнішньої дії на нього потужних імпульсних електромагнітних завад, що містять високу напругу, великі
струми і сильні електромагнітні поля. Purpose. Implementation of brief analytical review of basic scientific and technical achievements in area of electromagnetic compatibility (EMC) and protection from destabilizing and striking
action of powerful electromagnetic interference (PEMI) of natural
and artificial origin of radioelectronic, electrical engineering and
electric power equipment. Methodology. Scientific methods of
collection, analysis and analytical treatment of scientific and
technical information in a sphere EMC and such areas of knowledge’s as radioelectronics, electrical engineering and electric
power engineering. Results. A brief scientific and technical review
is resulted modern positions problems EMC and protection of
equipment from action on them PEMI. It is shown that PEMI can
result in failures in-process and death of examined equipment.
Annual harm in the industrially developed countries of the world
from the striking affecting of PEMI modern equipment with integral microcircuits and semiconductor devices can make ten of
milliards of USD. The basic methods of protection of equipment
are resulted from PEMI and protective devices (PD), intended for
the increase of effectiveness of modern equipment to the action of
external PEMI. Principles of work of the resulted PD and their
basic technical descriptions are described. Originality. On the
basis of materials of scientific monographs, journal publications,
normative documents and internet-reports systematization of basic PD, in-use presently in an area EMC and protection of different equipment from the hazard agency of external PEMI is executed. Practical value. Popularization of scientific and technical
knowledge’s in an area EMC and protection of modern equipment
from a dangerous action on them PEMI. Formulation of important for society scientific and technical problems and tasks, arising up in an area EMC and providing of the reliable functioning
of modern equipment in power electromagnetic interference